Factores de riesgos psicosociales y niveles de estrés en trabajadores administrativos de la Universidad de la Costa CUC en el 2014 (2014)
The present study aimed to characterize the psychosocial risk factors Intra and Extra Labor, and Individual Stress levels of administrative University –“Universidad de la Costa, CUC, based on quantitative research sectional descriptive. The sample consisted of 227 administrative institution of the University. The main purpose of this study was used as assessment instruments battery Psychosocial factors designed by the Ministry of Social Protection. Then the contextualization of the results at the level of each risk factor was performed, showing the findings through graphs of the main results in the medium, high and very high levels in each of the psychosocial factors, then the findings and intervention strategies and promotion of occupational factors and stress reduction are presented. Among the results highlights that the main risks in medium, high and very high levels are found: In the Intralaboral construct: Domain Control of Work, Leadership and Social Relations in the dimensions: Consistency Role, Demands of Work Session , Influence of Work on non- occupational Environment, Training, Participation and change Management, Role Clarity, leadership characteristics, social relations at work and performance feedback. In the non- occupational construct dimensions: Characteristics of the home and its environment, housing Shift work and time out of work. It is concluded that because of the domains and dimensions mentioned irrigation in advance of the administrative Coast University have symptoms related to stress in a risk level of 58%, so it is pertinent to make immediate interventions to promote the welfare of administrative employees.